The master term in Duflo-Zuker inspired mass formulas - Barbero, César Alberto (2012)
We present a detailed analysis of the term containing the information about monopolar interaction in Duflo-Zuker inspired mass formulas, usually known as the 'master term'. We discuss the physics involved in this master term and carefully study its asymptotic behavior with the aim of properly describe shell effects. We explore different dependence of the master terms with shell degeneracies. Ideas to improve the fits of experimental data in the future are shared.